2021
DOI: 10.4067/s0719-81322021000200115
|View full text |Cite
|
Sign up to set email alerts
|

Is the effectivity of copper ions treatment of milk enough to block Mycobacterium avium subsp. paratuberculosis infection in calves?

Abstract: Milk is an important transmission route of Mycobacterium avium subsp. paratuberculosis (MAP) for dairy calves. Given its resistance to pasteurization, alternative milk treatments are needed to control MAP transmission via milk. The present study reports the evaluation of a novel milk decontamination treatment based on copper ions as a means of preventing infection in dairy calves. Ten newborn calves were assigned to one of two experimental groups (n=5) which were studied for 1 year. The first group was fed mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Wolschendorf et al [9] also demonstrated that copper tolerance is associated with pathogen virulence. Steuer et al [14,44], on the other hand, demonstrated that although copper ions are highly effective in reducing the number of MAP in milk intended for calves, some MAP cells survived this copper-based treatment and were associated with greater evidence of pathology in these calves. Therefore, more studies should explore whether copper treatments are selecting more virulent MAP strains as described with many antibiotics [45].…”
Section: Discussionmentioning
confidence: 99%
“…Wolschendorf et al [9] also demonstrated that copper tolerance is associated with pathogen virulence. Steuer et al [14,44], on the other hand, demonstrated that although copper ions are highly effective in reducing the number of MAP in milk intended for calves, some MAP cells survived this copper-based treatment and were associated with greater evidence of pathology in these calves. Therefore, more studies should explore whether copper treatments are selecting more virulent MAP strains as described with many antibiotics [45].…”
Section: Discussionmentioning
confidence: 99%